The Pursuit of Excellence and the Role of Philosophy (2014)
David Robertson, the American conductor, addressing his audience while conducting the 2009 Last Night of the Proms, reflected on the makeup of his orchestra: "When looking at strife in the world, and for examples of overcoming it, just think of the orches